Iteractive methods for solving degenerate system of grid equations - Á, Đặng Quang (Journal of Computer Science and Cybernetics, 2016)
In this paper we construct an iteractive method for solving degenerate system  of  grid equations and after that we use parametric extrapolation technique for accerlerating its  convergence rate. The  efficiency of the method is shown on examples.